Thermoplastic Epoxide Resin in the Presence of Polyethylene Glycol as Hot-melt Adhesive in Clean Technology - Mukherjee, G.S.; Shukla, N.; Singh, R.K.; Mathur, G.N. (Defence Science Journal, 2004)
Pollution caused by the process involving handling of solvents is considered as one of the most serious ecological problems. In this perspective, thermoplastic epoxide resins were synthesized from the controlled reaction of bisphenol A, epichlorohydrine, and 3,5 dimethylaniline with a view to prepare ingredients for hot melt adhesive) was designated as HMA/(Subscript)35' Addition of polyethylene glycol (20 Wt per cent) of molecular weight 6000 (PEG6K) in the blend was found to be optimum towards providing maximum tensile lap shear strength with reference to aluminium/adhesive/aluminium bonding with a value of 5.05MPa. The matrix of the blend remains optically transparent till the content of PEG6K remains up to 20 Wt per cent; however beyond 20 Wt percent of PEG6k, the matrix becomes opaque with the appearance of spherulities due to presence of excess PEG6K in the blend. Interestingly, blends containing <= 20 Wt percent PEG6K showed no endotherm below 100 (Degree)C even though the melting point of pristine PEG6K is 55 (degree)C. FTIR data revealed the interactive role of PEG6K with the epoxide resin.